SYSTEMATIC LITERATURE REVIEW: KINERJA SISTEM INFORMASI AKUNTANSI RUMAH SAKIT di INDONESIA - Lina Amelia; Dwi Cahyono; Elok Fitriya (Juremi: Jurnal Riset Ekonomi, 2021)
This study is about the factors that affect the performance of accounting information systems in hospitals in Indonesia. By using a systematic literature review method which consists of three stages, namely, planning, implementation, and reporting. The research data was obtained from Google Scholar which was published in 2013 to 2020, the initial study found in this study was 410 articles, and the total study used was 7 articles as data sources and will be analyzed further. This study only uses research with a quantitative approach. The results of a systematic literature review of all published studies state that the factors that affect the performance of accounting information systems in hospitals in Indonesia are very diverse, namely, user involvement factors, top management support, human resource capabilities, system development, and education and training programs. The main influencing factor is user involvement where hospitals should provide education and training programs for accounting information system programs so that they can improve user skills.